The Budget Law As a Mechanism of Government Intervention in the Economy in Light of The Adoption of Market Economy in Algeria - banoune, khir edine (Milev Journal of Research and Studies, 2016)
Algerian Adoption of the mechanisms and the principles of the liberal economy, as liberalization of foreign trade, open the way to the private sector, and the abandonment of the direct investment in the public firms. All that did not prevent Algeria for continuing to pursue the intervention policy in economic activity, through the budget law which authorizes and implements the public investment programs